2016
DOI: 10.5964/ijpr.v10i2.214
|View full text |Cite
|
Sign up to set email alerts
|

When and by whom are apologies considered? The effects of relationship and victim/observer standing on Japanese people’s forgiveness

Abstract: Existing studies report on tendencies for first-party victims of a transgression to be less considerate of apologies compared to third-party observers when deciding on forgiveness. The present research investigated the conditions in which such discrepancies arise, focusing exclusively on the factor of one's relational involvement with the transgressor. We presented Japanese participants (N = 116) with hypothetical cases of transgression, while varying on victim/observer standing, involvement with the transgres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Participants then responded to the following measures on a scale of 1 ( Fully disagree ) to 9 ( Fully agree ). For the retributive motivation, we used the revenge subscale of the Transgression‐Related Interpersonal Motivation (TRIM) Scale (Japanese translation by Hashimoto & Karasawa, 2016; originally by McCullough et al., 1997). With four items (α = .85), participants marked the extent to which they want the perpetrators to get a deserved treatment such as punishment.…”
Section: Methodsmentioning
confidence: 99%
“…Participants then responded to the following measures on a scale of 1 ( Fully disagree ) to 9 ( Fully agree ). For the retributive motivation, we used the revenge subscale of the Transgression‐Related Interpersonal Motivation (TRIM) Scale (Japanese translation by Hashimoto & Karasawa, 2016; originally by McCullough et al., 1997). With four items (α = .85), participants marked the extent to which they want the perpetrators to get a deserved treatment such as punishment.…”
Section: Methodsmentioning
confidence: 99%
“…Contrary to this, however, Hashimoto and Karasawa (2012) found that observers (but not victims) were more rather than less forgiving following coerced apology (i.e., when an offender apologized after the victim demanded it). The same researchers also later found that observers were generally more forgiving of sincere (vs. insincere) apologizers, whereas victims discriminated apology sincerity only when they were highly involved with offenders (Hashimoto & Karasawa, 2016).…”
Section: Prior Work On Coerced Apologies: Still No Clear Answersmentioning
confidence: 82%
“…Methodologically, several limitations of these previous studies also suggest more work is needed to understand how voluntary (vs. coerced) atonement affects third-party evaluations. First, coercion manipulations in past research have been relatively weak because interveners were offenders' peers who simply told them to apologize (Hashimoto & Karasawa, 2016;Risen & Gilovich, 2007) or a mediator who suggested that an apology might help (Robbennolt, 2013). Although reprimands from same-status peers are unfavorable, whether offenders felt "coerced" to apologize is questionable when serious consequences are absent (see Jehle et al, 2012).…”
Section: Prior Work On Coerced Apologies: Still No Clear Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…On what basis, then, will third-party observers decide that offenders deserve forgiveness? Apart from work on public confession (Cerulo & Ruane, 2014; Gold & Weiner, 2000; Weiner, Graham, Peter, & Zmuidinas, 1991) and victim-observer asymmetries in discriminating apology sincerity (Hashimoto & Karasawa, 2012, 2016; Risen & Gilovich, 2007), no studies to our knowledge have tackled this subject.…”
Section: Third-party “Forgiveness” Versus “Forgivability”mentioning
confidence: 99%